A pilot study characterizing tetrachloroethylene exposure with exhaled breath in an impacted community. (15th March 2022) - Liu, Sa; Yan, Eileen Ziyao; Turyk, Mary Ellen; Katta, Sankalp Srisai; Rasti, Arteen Fazl; Lee, Jung Hyun; Alajlouni, Marwan; Wallace, Thomas Edward; Catt, Wade; Aikins, Elizabeth Ann
Abstract: Martinsville, Indiana overlays four groundwater contamination plumes, including a U.S. Environmental Protection Agency (EPA)-designated Superfund site. The primary contaminants are tetrachloroethylene (PCE), trichloroethylene (TCE), and other volatile organic compounds (VOCs). Martinsville represents many similar communities facing the challenge of groundwater and soil contamination and vapor intrusion, where residents are often frustrated by the lack of help in understanding and addressing the problem. The objective of this study was to evaluate PCE in exhaled breath to identify and quantify exposure to PCE and to explore the extent and level of PCE exposure among community residents. We measured chlorinated VOCs in exhaled breath samples from 38 healthy individuals who lived either in a contamination area or outside any plume area. We also measured VOCs in indoor air and tap water samples collected from 10 homes. PCE was detected in all exhaled breath samples (mean: 6.6 μg/m 3 ; range: 1.9–44 μg/m 3 ) and tap water samples (mean: 0.74 μg/L; range: 0.39–0.92 μg/L). PCE was detected in six of nine (66%) homes with air concentrations ranging from 1.6 to 70 μg/m 3, exceeding the EPA action level of 42 μg/m 3 . We did not detect TCE or any other chlorinated VOCs in these samples. PCE exposure occurred among individuals living on the EPA Superfund site, as well as among those living on other plume sites and those living outside any known plumes. Preventive measures should focus on identifying highly exposed groups and reducing their exposures, followed by addressing moderately elevated exposures in the community. Our results demonstrated that PCE in exhaled breath can be used as an effective tool in community engaged environmental health research to evaluate the extent and level of community exposure, increase awareness, and promote residents' participation in research and site cleanup decision-making. Graphical abstract: Image 1 Highlights: Exhaled breath can be used to measure community exposure to tetrachloroethylene. Tetrachloroethylene was detected in the exhaled breath of 100% of participants. Vapor intrusion was determined to be the primary source of exposure. Testing exhaled breath promotes participation in community-engaged research.